2001
DOI: 10.1530/eje.0.1450737
|View full text |Cite
|
Sign up to set email alerts
|

Increased leptin and tumour necrosis factor alpha per unit fat mass in hypopituitary women without growth hormone treatment

Abstract: Background: The adipocyte products, leptin and tumour necrosis factor (TNF)a, are associated with atherosclerotic diseases and may be factors contributing to the enhanced cardiovascular risk in hypopituitary patients with growth hormone (GH) deficiency. Objective: To investigate whether leptin and TNFa are increased in a group of hypopituitary women previously found to have increased cardiovascular morbidity, and to compare them with matched individuals of the same sex and age and with similar body composition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 47 publications
(55 reference statements)
1
5
0
Order By: Relevance
“…On the other hand, there are studies supporting our findings in the literature [7,12,28]. The results of the study by Serri et al [7], were similar to our findings as they found significantly higher basal TNF-a levels in GHD patients than controls and TNF-a levels decreased significantly at the end of 3 months' rhGH treatment in GHD.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…On the other hand, there are studies supporting our findings in the literature [7,12,28]. The results of the study by Serri et al [7], were similar to our findings as they found significantly higher basal TNF-a levels in GHD patients than controls and TNF-a levels decreased significantly at the end of 3 months' rhGH treatment in GHD.…”
Section: Discussionsupporting
confidence: 92%
“…The ages of children in GHD groups in this study and our study were very similar (12.7 ± 2.5 years in treated GHD and 13.0 ± 2.6 years in untreated GHD in Lanes et al's study and 12.60 ± 2.27 years in our study). In hypopituitary women without GH treatment, higher serum TNF-a levels per unit fat mass were demonstrated according to controls [28]. GH administration had also been shown to lower serum TNF-a levels in children suffering from burns [29].…”
Section: Discussionmentioning
confidence: 99%
“…These results have paralleled studies of children suffering from burns (Chrysopoulo, Jeschke, Ramirez, Barrow, & Herndon, 1999) and cystic fibrosis (Hardin et al, 2001) in that GH administration resulted in a marked decrease in TNF-α levels among both patient populations. Hypopituitary women without GH treatment have also demonstrated clinically elevated TNF-α levels per unit of fat mass as compared with control subjects (Bulow, Ahren, & Erfurth, 2001). Importantly, both IGF-1 and GH have been shown to increase throughout the course of normal childhood development, peaking at approximately Tanner stages (TSs) III and IV (i.e., during puberty; Veldhuis, Roemmich, & Rogol, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…With insulin resistance possibly contributing the greatest risk of premature cardiovascular disease, 12 many recent studies have now examined the role of adipocytokines, such as adiponectin 4 and tumour necrosis factor‐α (TNF‐α), 13 as other possible predictors of future cardiovascular events. Low adiponectin levels have been reported in type 2 diabetes 14 and the metabolic syndrome, 15 whereas high TNF‐α levels are reported in obese 16 and GH‐deficient adults 13 . As inflammation is also implicated in the pathogenesis of atherosclerosis, 17 surrogate markers of inflammatory activity such as C‐reactive protein (CRP) and interleukin‐6 (IL‐6) have been shown to predict the risk of cardiovascular events in healthy subjects 18 .…”
Section: Introductionmentioning
confidence: 99%